THE IMPROVING OF THE QUALITY OF REMELTING CONTAMINATED ALUMINUM SHAVINGS - Mytiaiev, O. O. (Science and Transport Progress, 2008)
The ways of increasing of constructional strength of secondary aluminium alloys up to the level of strength of primary ones are considered.